Evaluating stakeholders’ preferences: Reconciling heritage and sustainability in Kuala Lumpur traditional areas - Wan Abdullah Zawawi, Noor Amila; Abdullah, Alias (Malaysian Institute of Planners, 2011)
Unchecked redevelopments are destroying our unique multi-cultural heritage. The subsistence of this built heritage is threatened by demolition, unsympathetic changes and rapid redevelopment pace. Escalating market value increasingly replaces these buildings with newer and higher density structures. Most often, the decisions pertaining to traditional shophouse redevelopment are based on guidelines inherited from the mono-cultural British system, whose perspectives narrowly represent the multi-cultural society in Malaysia. On top of that, involvement of direct stakeholders, namely owners and tenants, are minimal in the decision process. This paper is part of an ongoing research to provide an objective evaluation for traditional shophouse redevelopment, incorporating multiple stakeholders’ preferences. It focuses on exploring conflicts and values of the stakeholders using Multiple Criteria Analysis, or MCA technique. Using a common MCA technique, the Analytical Hierarchy Process, or AHP, stakeholders’ preferences on a set of criteria for redevelopment decision are derived and compared. It is found that stakeholders’ preferences are dissimilar even within their homogenous groups. This study contributes to discovering the potential of MCA to increase transparency in redevelopment decisions involving built heritage and multiple stakeholders.